Community engagement and loneliness in older adults in China: mediation effects of social support in the wake of COVID-19 - Xie, Xiaoxia; Huang, Chienchung; Sitar, Sophie; Qiao, Xingyong (Frontiers in Public Health, 2023)
Drawing from the ecological model of aging, the active aging perspective, and the convoy model of social relations, this study investigates the extent community engagement influences loneliness and whether the relationship is mediated by social support during the COVID-19 pandemic. Data was collected from 1,067 retired older adults in a cross-sectional design in Chengdu, China in 2022. The results show community engagement was positively associated with social support (β=0.26, p<.001) and social support was negatively related to loneliness (β=-0.41, p<.001). Social support fully mediated the relationship between community engagement and loneliness. Additionally, community engagement had an indirect effect on loneliness via social support (β=-0.11, p<.001). The findings from the moderation analysis suggests community engagement and social support are likely to have large effects on loneliness for older adults over the age of 70 and who have low educational attainment. The findings suggest community engagement could be an important factor for improving social support and reducing loneliness amongst retired, older adults in China, especially in the wake of the COVID-19 pandemic where millions of individuals were isolated for extended periods of time.